Readings in environmental ethics : multidisciplinary perspectives - Srivastava, D. C. (Rawat Publications, 2005)
Contributed articles; in the Indian context. "This book contains reflective essays on various aspects of environmental awareness in contemporary times. Though contemporary in spirit, many of these essays also draw upon timeless traditional insights, both from the eastern and the western traditions. The book is conceived from the standpoint of multi-perspectival approach to the concept of environment. It is intended for readers who are, at many times, desperately in need of an understanding of the idea of environment much more holistic than what other books on this issue usually provide. Currently enthusiastic research and widespread deliberations on this issue of environment would, it is believed, gain immensely from the multi-dimensional approaches presented in this book. The contributors are drawn from diverse intellectual preoccupations ranging from Philosophy, Religion, Sociology, Biology, Physics to Literature."